PENINGKATAN KETERLIBATAN SISWA MELALUI MEDIA KARTU OPERASI HITUNG DALAM PEMBELAJARAN MATEMATIKA: STUDI PTK DI WILAYAH PERBATASAN - Lidwina C. Maniboey; Suwita; Aisyah Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Student engagement is a crucial component of meaningful learning, particularly in basic mathematics subjects that require active participation and conceptual understanding. This study aims to evaluate the effectiveness of using arithmetic operation cards in enhancing elementary students’ engagement in learning multiplication factors. The research employed a Classroom Action Research (CAR) approach over two cycles, conducted at SD Negeri Inpres Skouw Mabo, Papua, involving 21 students from grades IV and V. Data were collected through observation, field notes, and teacher journals, and analyzed both quantitatively (Wilcoxon test) and qualitatively (thematic analysis). The findings indicate a significant improvement in students’ behavioral, emotional, and cognitive engagement, with average scores increasing from 56.05 (baseline) to 62.17 (cycle 1), and 69.05 (cycle 2) (p < 0.001). Qualitative data support these results by showing positive changes in students’ participation, enthusiasm, and thinking strategies. This study confirms that simple manipulative media such as arithmetic operation cards can serve as an effective alternative to enhance student engagement, particularly in areas with limited educational resources.